Strategy of managing cultural diversity to develop creativity in a learning organization - SETOUTAH, S; JELJELI, R (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to identify strategies to manage cultural diversity and develop creativity at “Fertial Company” in Algeria, following a partnership with a Spanish partner that caused intercultural communication problems among multicultural competencies. As a solution, managers have worked on cultural diversity management methods to support external pressures arising from the external environment and internal pressures related to the functional combination of Cultural backgrounds. The study finds that multiculturalism enhances human and organizational capital, leads to organizational flexibility, and leads to creativity, multiple options, creative alternatives, and solves problems efficiently. RESUMEN Este estudio tiene como objetivo identificar estrategias para gestionar la diversidad cultural y desarrollar la creatividad en "Fertial Company" en Argelia, luego de una asociación con un socio español que causó problemas de comunicación intercultural entre competencias multiculturales. Como solución, los gerentes han trabajado en métodos de gestión de la diversidad cultural para soportar las presiones externas derivadas del entorno externo y las presiones internas relacionadas con la combinación funcional de los fondos culturales. El estudio encuentra que el multiculturalismo mejora el capital humano y organizacional, conduce a la flexibilidad organizacional y conduce a la creatividad, múltiples opciones, alternativas creativas y resuelve problemas de manera eficiente.